2022
DOI: 10.1097/01.gox.0000842644.34370.fb
|View full text |Cite
|
Sign up to set email alerts
|

81. The Effect of Masculinizing Hormone Therapy On Wound Healing in Sterilized Mice

Abstract: sense any stimuli on their nipples, a thicker monofilament size was required (4. 45-4.46, p=0.00037-0.002). Conclusion:Postoperative sensation is normal except on the nipple, inframammary scar, and mid-axillary line. The inframammary scar is located along the dermatome of the 4th intercostal nerve that is routinely resected in DM-FNGs. Patients with large breasts have gravitational traction injury of their intercostal nerves with concomitant binding due to gender dysphoria have decreased sensation at baseline,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Lastly, more evidence regarding the effect of different HRT agents on operative outcomes such as infection or scar formation is required as some preliminary studies showed that testosterone may affect wound healings or cause hypertrophic scars. 18,19 In addition, there is a lack of literatures comparing the route of HRT administration on perioperative risk and effect of HRT on aging transgender and gender-diverse adults. 20 Such investigations are outside the scope of this study but will help to shed lights on the ongoing debate of perioperative HRT usage and should be weighed when making an expert consensus.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, more evidence regarding the effect of different HRT agents on operative outcomes such as infection or scar formation is required as some preliminary studies showed that testosterone may affect wound healings or cause hypertrophic scars. 18,19 In addition, there is a lack of literatures comparing the route of HRT administration on perioperative risk and effect of HRT on aging transgender and gender-diverse adults. 20 Such investigations are outside the scope of this study but will help to shed lights on the ongoing debate of perioperative HRT usage and should be weighed when making an expert consensus.…”
Section: Discussionmentioning
confidence: 99%